Peran guru dalam meningkatkan keterampilan berpikir tingkat tinggi siswa kelas awal pada pembelajaran tematik di sekolah dasar - Ahmad Fajar Awalushihab; Rora Rizki Wandini; Kholidtur Rahman Lubis (Jurnal Pendidikan Dasar, 2025)
The role of the teacher is very important in the world of education, because the teacher is in charge and responsible for motivating, facilitating, educating and training students. This study aims to make students active in thinking and carrying out learning so that students are happy and active in answering questions by the teacher. Teachers teach with methods that make students active in carrying out learning so that students are happy and active in learning answer questions by the teacher. The type of research used in this research is descriptive qualitative which is narrative in nature. The research results are in the form of a descriptive description. One way to overcome the difficulties experienced by students is to increase students' learning interest in lessons that students experience difficulties, with interest, it is hoped that students can study well and be able to overcome the difficulties students experience.